Diversity of Gastropod in the Seagrass Ecosystem on the Coastal Area of Nirwana Beach, Padang, Sumatera Barat Province - Arifah, Mukhlisa Dieni; Fajri, Nur El; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Nirwana beach is one of tourist destinations in the Sumatera Barat Province. The input of pollutant originated from anthropogenic activities, however, reducing the water quality and as a consequence negatively affects the seagrass ecosystem as well as the associated organisms, including gastropods. To understand the diversity of gastropod in the seagrass ecosystem and the water quality, a research was conducted on September 2016. There were 3 stations and in each stations there were 3 lines. In each line, 5 quadrants (1 x 1 m2) were placed. Gastropods present inside the quadrant were sampled manually. Results shown that there were 16 gastropods species present, they were Cerithium asper, C. litteratum, C. lutosum, Clithon sp., Clypeomorus bifasciata, Columbella sp., Conus sp., Cypraea sp., Morula margariticola, Nassarius sp., Natica sp., Nerita histrio, N. squamulata, Polinices tumidus, Strombus sp. and Turbo sp. The value of diversity index (H’) was 2.193-2.370 and the dominance index (C) was 0.2485-0.3147. The water quality parameters are as follows : temperature was 30-31 0C; depth was 0.24-0.54 m; pH was 8; salinity was 33.3 0/00 and DO was 4.20-6.35 mg/L. Data obtained indicate that the diversity and the water quality in the Nirwana Beach is good and able to support the life of gastropods.Keywords: Diversity, Gastropods, Nirwana Beach, Seagrass EcosystemPENDAHULUANPantai Nirwana terletak di Kecamatan Lubuk